Impact of High-Fat Diet in Early-Life on Mammary Metabolic and Inflammatory Status in Later-Life in Mice. (7th June 2021) - Tang, Ying; Lin, Ting-Chun; Chung, Soonkyu; Kim, Young-Cheul; Liu, Zhenhua
Abstract: Objectives: Emerging evidence indicates a potentially important role for early-life events and exposures in cancer development later in life. Moreover, accumulating evidence suggests that the incidence of cancers has reached a plateau in elders, whereas it continuously rises in young to middle adult. The present study aimed to investigate the potential impacts of high-fat diet in early-life, mimicking childhood/adolescent in humans, on mammary health in later-life of mice, equivalent to the young to middle age in human. Methods: Female C57BL/8 mice (4 weeks of age) were fed a low-fat diet (LF: 10% kcal from fat) or a high-fat diet (HF: 60% kcal from fat) for 8 weeks, which is equivalent to child/adolescent age in humans. Mice in early-life groups were sacrificed after 8 weeks feeding, whereas mice in later-life groups were switched to standard chow diet (Lab Diet#5P76) and fed for additional 12 weeks before sacrifice. A panel of metabolic parameters, inflammatory cytokines, as well as gene expression related to tumorigenic Wnt -signaling were assessed by qPCR and immunoblotting analysis. Results: Compared with LF group, the body weight in HF group was significantly elevated after 8-wk HF diet feeding ( P < 0.05). After switching to the standard chow diet for 12 weeks, the significance remained until 24 weeks of age although with a reduced degree of magnitude ( P < 0.05). For the metabolic factors, HFD reduced the expression levels of both Pparγ ( P  = 0.08) and adiponectin ( P < 0.05) at 12 weeks and the reductions remains at 24 weeks ( P < 0.01). Meanwhile, expressions of aromatase, estrogen receptor α and Tnf-α, Il-6, Il-10 as well as Cox2 among examined inflammatory mediators ( Tnf-α, Il-6, Il-10, Il-2, Il-1β, Ifn-γ, Cox2 ) were significantly higher in HF than in LF group at 24 weeks ( P < 0.05). For Wnt-signaling target genes ( Cyclin D1, C-Myc, and Axin 2 ), a significant increase for C-Myc was observed in HF group at 12 weeks ( P < 0.01). Conclusions: Our results suggested that HF diet in early-life enhances adiposity and alters mammary metabolic and inflammatory status, creating a microenvironment in favor of breast tumorigenesis in later-life. Funding Sources: This project was supported by USDA/Hatch (#1013548).